„A debreceni presbitérium igen nagy célra van elhívva…” Vitás ügyek a debreceni presbitériumban az 1920-as évek első felében - Dávid KIS (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica, 2023)
“The Presbytery of Debrecen Is Called to a Great Purpose...” – Controversial Issues in the Presbytery of Debrecen in the First Half of the 1920s. The Reformed congregation of Debrecen was the largest and most famous local church at that time in Hungary. More than 70,000 Reformed citizens lived in Debrecen. The presbytery consisted of 100 members. The presbyters of Debrecen felt a responsibility not only for their congregation but for the whole Hungarian Reformed Church, even when the local church was in an extremely difficult situation after the World War I – financial crises, political storms, problems in administration and organization. This paper aims to give an insight into the functioning of the presbytery, with particular reference to controversial issues. In several articles and conferences, the presbyters dealt with the office of the presbyter, its development, historical examples, the presbyters’ tasks, and the election method. In addition, two longer papers were published, which dealt with the congregation’s problems and possible solutions. Besides all this, the church taxes – which generated heated debates – were the critical issues in the life of presbytery. I believe the mentioned issues are still relevant for our church, so we should draw certain conclusions from these.